Prevalence of proximal contact loss between implant-supported prostheses and adjacent natural teeth: A systematic review and meta-analysis - Bento, Victor Augusto Alves [UNESP]; Gomes, Jessica M.L. [UNESP]; Lemos, Cleidiel A.A.; Limirio, João P.J.O. [UNESP]; Rosa, Cleber D.D.R.D. [UNESP]; Pellizzer, Eduardo P. [UNESP] (Elsevier, 2021)
Statement of problem: Proximal contact loss between implant-supported prostheses and adjacent natural teeth is a complication that has been reported in clinical practice. However, the prevalence of the condition is unclear. Purpose: The purpose of this systematic review and meta-analysis was to assess the proportion of reported proximal contact loss between implant-supported prostheses and adjacent natural teeth. Material and methods: This systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology criteria and was registered on the international prospective register of systematic reviews (PROSPERO) platform (CRD42021225138). The electronic search was conducted by using the PubMed/MEDLINE, Embase, and Cochrane Library databases to September 2020. The formulated population, intervention, comparison, outcome (PICO) question was “Is there a correlation of the proximal contact loss between implant-supported prostheses and the adjacent natural tooth?” A single-arm meta-analysis of proportion was performed to evaluate the cumulative prevalence of survival and complication rates. Results: This review included 10 studies, half of which presented proximal contact loss rates higher than 50%. In the general analysis, the open proximal contact showed a cumulative proportion of 41% (confidence interval: 30% to 53%; heterogeneity: I2=98%; t2=0.578; P<.01). From the subanalysis, the mesial contact (47%; confidence interval: 32% to 62%; heterogeneity: I2= 96%; t2=0.657; P<.01) and the mandibular arch (41%; confidence interval: 30% to 52%; heterogeneity: I2=92%; t2=0.302; P<.01) were found to have higher prevalence. Conclusions: The prevalence of proximal contact loss was high, occurring more frequently with the mesial contact and in the mandibular arch. Significant differences were not found in relation to sex or between the posterior and anterior regions.